Eu-topos / ou-topos: utopías y futuro - Serafin, Silvana (Oltreoceano - Rivista sulle migrazioni, 2021)
El objetivo de este estudio es demostrar cómo las utopías recuperan la posesión de un microcosmos circunscrito que adopta los contornos de la isla evocados por el canon de la escritura utópica reactivando el sueño de llegar al hermoso lugar, el eu-topos que prevalece sobre el concepto de ou-topos, el lugar que no existe. Eu-topos / Ou-topos: Utopias and the Future The aim of this study is to demonstrate how utopias reclaim a circumscribed microcosm that takes the contours of the island evoked by the canon of utopian writing. It also shows how they reactivate the dream of reaching eu-topos, the beautiful place which thus prevails over the concept of ou-topos, the place that does not exist.